Challenges and opportunities of cfDNA analysis implementation in clinical practice: perspective of the international society of liquid biopsy (ISLB) (2020)
Precision medicine was born with the development of new diagnostic techniques and targeted drugs, yielding better outcomes in cancer care. With the evolution and increasing sensitivity for detecting oncogenic drivers, liquid biopsies (LBs), specifically cell-free DNA (cfDNA) analysis, have been proposed as a minimally-invasive technique for genomic profiling. Ranging from sequencing techniques to PCR-based methods and other more complex strategies, this approach, currently applicable in some solid tumors with robust evidence, is showing promising opportunities in other cancers. However, difficulties in validating their clinical utility exist within limitation at different levels among several techniques, reporting of the results, lack of appropriate clinical trial designs, and unknown economic impact. One of the aims of the ISLB is to create recommendations to develop reliable and sustainable diagnostic, prognostic and predictive tools using LBs. This paper is addressing these objectives, helping the healthcare providers and scientific community to understand the potential of LB.